Anti-Liver membrane Antibody predict outcome of Autoimmune Hepatitis - AL- Obeidy, Eman Sh.; Al-Haidary, Batool A.; Najeeb, Akram A. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Autoantibodies against liver membrane are the specific autoantibodies found in AIH. Cytochrome P450 1A2 has been identified as thetarget autoantigen for these autoantibodiesThe aim of the study : is to evaluate the prevalence and clinical relevance of LMA in AIHMethods: The study was performed on 73 Iraqi patients with chronic active hepatitis (CAH) of unknown cause , attending the teaching hospital for gastroenterology andliver disease in a period between November 2003 and July 2004. Anti-liver membrane antibodies were studied by IFA technique.Results: LMA was detected in the sera of 28(57.14)and 3(37.5%) patients with type 1 and type 3 AIH respectively, but never in the sera of healthy group .Conclusion: It was concluded that LMA is present in type-1 and type-3 AIH but not in sera of patients with type-2 or in healthy control group.